Yolk sac diameter as a prognostic factor for first trimester pregnancy outcome - Bhattarai, Anupama; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To evaluate yolk sac diameter as a predictor of first trimester pregnancy outcome. Methods: This was a prospective observational study conducted at Paropakar Maternity and Women’s Hospital from October 2017 to October 2018. Pregnant women in between seven and ten weeks of gestation were enrolled. Transabdominal sonography was performed to measure yolk sac diameter and followed up till 12 weeks of gestation to see the outcome. Sensitivity, specificity, positive predictive value and negative predictive value were calculated for yolk sac diameter with regards to abnormal pregnancy outcome. Results: There were 80 cases enrolled and a significant positive correlation was found between yolk sac diameter and gestational age. Abnormal yolk sac diameter, irrespective of gestational age, had sensitivity of 92.95%, specificity 66.66%, positive predictive value 95.6% and negative predictive value of 54.54% in predicting abnormal pregnancy outcome. Conclusions: The measurement of yolk sac diameter between seventh and tenth weeks of gestation can predict first trimester pregnancy outcome. This is useful while counseling pregnant women regarding risk of abnormal outcome and need for follow up ultrasonography. Keywords: first trimester; pregnancy outcome; prognostic factor; yolk sac diameter